Implementing malay language in linguistic steganography / Amirulikhsan Zolkafli and Roshidi Din - Zolkafli, Amirulikhsan; Din, Roshidi (2004)
Steganography, a part of information hiding is an art of hiding information into another medium of information (text, audio, video, image, etc ) with the main purpose is securing information during communication. With the purpose of opening an opportunity to create a communication channel that is covert and subliminal between two parties where by the existence of the particular message being sent and received are kept unknown or innocuous to any possible attacker. Steganography can be divided into two that is technical steganography and linguistic steganography. English have been widely used in linguistic steganography. Therefore, the main objective of this paper is to see whether other languages are compatible to be implement as linguistic steganography. This paper will discuss briefly on linguistic steganography and its system model. The comparison study is done based on linguistic aspects (syntactic and semantic) of several foreign language that have been developed into machine translation system. Chinese, Japanese, and Malay will be compared, in which the characteristic of Malay language will be highlighted in this paper. We will be discussing the purpose of using its language structure to hide secret information in it. This is to show several characteristic of Malay language that could be used in linguistic steganography. Finally, this paper by mentioning the general potential of information hiding and the impact in the form of applications that it could give to Information and Communication Technology (ICT) environment.